Identity and Personality Pathology in Adult Forensic Psychiatric Patients and Healthy Controls - Tressová, Deni (International journal of offender therapy and comparative criminology, 2024)
Since the publication of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), identity impairment has become a diagnostic criterion for all personality disorders. The current study examined the occurrence of identity dimensions, clinically relevant identity impairments and personality pathology, and associations between these constructs in 92 forensic patients and 139 healthy controls. Patients showed higher levels of almost all identity dimensions, identity impairments, personality disorders, and almost all maladaptive personality traits than controls. Various identity dimensions were associated with consolidated identity as well as identity impairments in both groups. Both patients and controls with high ruminative exploration and identity malfunctioning showed more personality pathology. Different associations between identity functioning and particularly antisocial and borderline personality disorder showed to be stronger in patients than in controls. Our results highlight the importance of identity impairment as a crucial criterion to assess and treat personality pathology in forensic patients.